El panorama a nivel mundial de la investigación en productos forestales - Kauman, Walter G. (Instituto de Ecología, A.C., 2016)
Wood has long been one of the materials most used by humankind. Currently, the technology related to its use is undergoing a rapid transformation owing to the tremendous increase in the use of computers. This is affecting all branches of the forest industry, from taxonomic identification to the determination of wood properties and drying methods. Research has produced a plethora of new data and has resulted in the creation of international exchange entities such as IUFRO. Current trends in research are directed towards the improvement of manufacturing processes and their impact on the environment. Wood is being recognized as the renewable material most appropriate for the protection of the environment. Wood reduces our dependence on fossil fuels and reduces the greenhouse effect through the fixation of huge amounts of gaseous carbon in the woody tissue of new plantations. The low energy requirements for the transformation of wood into products and its possibilities as a bio-material foretell benefits for the future.